2015
DOI: 10.1111/vde.12253
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of FEDESI and SCORFAD scoring systems for the evaluation of skin lesions in allergic cats

Abstract: Only improvement percentage of FeDESI and SCORFAD scores seem to correlate well. SCORFAD is the only scoring system to have been validated, although it seems to correlate less with pruritus and may be more difficult to use than FeDESI. The latter could thus be more appropriate for use, but further studies are needed especially in regard to its validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 11 publications
2
19
2
Order By: Relevance
“…Although in the validation trials for those scores, there was a correlation between lesions and pruritus, there are allergic individuals that itch yet do not show lesions. This is further supported by studies in cats and dogs that describe only a poor correlation between lesions and pruritus . In the present study, clinical lesions clearly and prominently responded to treatment in many horses, whereas pruritus was not significantly altered.…”
Section: Discussionsupporting
confidence: 87%
“…Although in the validation trials for those scores, there was a correlation between lesions and pruritus, there are allergic individuals that itch yet do not show lesions. This is further supported by studies in cats and dogs that describe only a poor correlation between lesions and pruritus . In the present study, clinical lesions clearly and prominently responded to treatment in many horses, whereas pruritus was not significantly altered.…”
Section: Discussionsupporting
confidence: 87%
“…To date, SCORFAD (scoring feline allergic dermatitis) is the only validated scoring system used in cats . We used a modified FeDESI because SCORFAD was not available at the time of this study.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, as for dogs with allergic disease, objective scoring tools have been described to evaluate the severity of skin lesions in feline allergic dermatitis, such as the FeDESI and the SCORFAD . Of these, only the latter was validated, although in a comparative study the former was considered to correlate better with pruritus . On the other hand, no tool for the evaluation of pruritus has been developed specifically for cats and investigators usually adopt the canine VAS for cats …”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Of these, only the latter was validated, although in a comparative study the former was considered to correlate better with pruritus. 21 On the other hand, no tool for the evaluation of pruritus has been developed specifically for cats and investigators usually adopt the canine VAS for cats. 18 In this study QoL scores showed a moderate and significant correlation with pruritus, but did not correlate with FeDESI or to SCORFAD.…”
Section: Discussionmentioning
confidence: 99%